Women's leadership in Ethiopian higher education: development, contribution, quality and preference - Abebaw Yirga Adamu (College of education, Bahir Dar University, 2023)
Women are underrepresented in higher education leadership across the world and Ethiopia is no exception. Although women leadership in Ethiopian higher education is a relatively new practice, its development has not been well examined. The present paper aims to address this lacuna by examining women senior leadership development, contribution, quality and preference based on the views and experiences of twelve women senior leaders drawn from ten public universities. The participants are current and past vice presidents at public universities of different generations and types. The results indicate that although women have made significant progress in gaining senior leadership positions, senior leadership remains to be a men's club where women are rarely invited. The results also reveal that women have perceived leadership quality and contributions. The findings show that among the various senior leadership positions women prefer and assume a research and community service vice president position and this goes to the extent of associating this position with women. The results suggest that enhancing women leadership development requires providing training, mentoring and other opportunities specifically aimed at advancing women to senior leadership positions, and ensuring sustainability of women leadership development programs.